Therapeutic Strategies for Heart Failure (Springer Japan, 2018)
This book introduces pathophysiology and practical heart failure (HF) management at the acute, in-hospital stages during hospitalization and also in the end-stages of HF. Given its increasing incidence and prevalence, we live in a world that is essentially facing an HF pandemic. A country with an ageing population, Japan is unique in terms of the selection of medical treatment, diagnostic techniques, team managing and other approaches. This book sheds new light on the clinical challenges involved in reducing re-hospitalization and improving patients' prognosis and ADL/QOL, while also reporting on the status quo in Japan. By highlighting these challenges and the methods used to address them, it will encourage experts around the globe to intensively discuss and accelerate research in this field. Including contributions by authors who have played central roles in managing HF in Japan, the book offers an indispensable guide not only for clinicians, technicians and nurses in this field, but also for general physicians, emergency physicians and all others who are involved in the management of acute and end-stage HF.